Pengaruh Kompetensi Kerja, Budaya Kerja, Dan Motivasi Terhadap Kinerja Petugas Puskeswan Pada Dinas Peternakan Dan Kesehatan Hewan Kabupaten Tulungagung - Tutus Sumariyani; Arisyahidin Arisyahidin (Otonomi, 2022)
Employees as the source of the way for the organization, enable the functioning of an organization and become the most important element in management. Therefore, the role of humans is very important in achieving the goals of an organization. This study aims to: (1) analyze the variables of competence, work culture, and work motivation have a simultaneous effect on the performance of the Puskeswan Officers, (2) analyze the competence variables partially influence the performance of the Puskeswan officers, (3) analyze the variables of work culture that have a partial effect on Partial to the Performance of Puskeswan Officers, (4) Analyzing work motivation variables that partially affect the Performance of Officers' Employees, (5) Analyzing which variables of competence, work culture, and work motivation have the dominant influence on the Performance of Puskeswan Officers. This study uses quantitative analysis methods, namely the analysis of data that has been scored according to a predetermined measurement scale using statistical formulas. The analysis used on data in the form of numbers. While the data analysis method used: (1) descriptive statistical analysis, (2) classical assumption test, and (3) inferential statistical analysis. The results showed that: (1) Competence, Work Culture and Motivation had a significant influence on the performance of Puskesmas Officers at the Department of Animal Husbandry and Animal Health, Tulungagung Regency. (2) Competence has a significant influence on the performance of Puskesmas officers at the Department of Animal Husbandry and Animal Health, Tulungagung Regency. (3) Work culture has a significant effect on the performance of Puskesmas officers at the Department of Animal Husbandry and Animal Health, Tulungagung Regency. (4) Motivation has a significant effect on the performance of Puskesmas Officers at the Department of Animal Husbandry and Animal Health, Tulungagung Regency. (5) Motivation has the most dominant influence on the Performance of Health Center Officers at the Livestock and Animal Health Service of Tulungagung Regency.